The contribution of human activities to climate changes - Camelia Slave; Carmen Man (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 3rd Edition of the International Symposium, October 2012, Bucharest, 2012)
Some of the components of the climate system, the oceans and biosphere primarily affects the concentration of greenhouse gases in the atmosphere. Plants take CO2 from the atmosphere and convert it in the process of photosynthesis, carbohydrate. In the industrial era, human activities have contributed to increased concentrations of greenhouse gases in the atmosphere. In addition, human activities contribute to climate change by altering the concentration of aerosols and clouds cover. Greatest contribution has fossil fuel that releases CO2 into the atmosphere. Impact of human activities on the climate is much higher than that of natural processes. The purpose of this paper is to show how the main compounds resulting from human activities contribute to climate change.
Keywords: 330; climate change; climate regions; greenhouse effect; global temperature; precipitation